2020
DOI: 10.3389/fgene.2020.00574
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA and mRNA Profile of Liver Tissue During Four Developmental Stages in the Chicken

Abstract: The liver is the major organ of lipid biosynthesis in the chicken. In laying hens, the liver synthesizes most of the yolk precursors and transports them to developing follicles to produce eggs. However, a systematic investigation of the long noncoding RNA (lncRNA) and mRNA transcriptome in liver across developmental stages is needed. Here, we constructed 12 RNA libraries from liver tissue during four developmental stages: juvenile (day 60), sexual maturity (day 133), peak laying (day 220), and broodiness (day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
6
6
0
Order By: Relevance
“…According to the present study, lncRNAs and mRNAs are expressed in a stage-dependent manner, consistent with previous studies [ 35 , 36 , 37 ]. The results of both hierarchical clustering and PCA showed that the GRI and MGI stages were more distinct than MGI and RSI stages at the mRNA or lncRNA level ( Figure 2 ), implying that a massive physiological change related to a shift in metabolism occurred during early muscle development.…”
Section: Discussionsupporting
confidence: 93%
“…According to the present study, lncRNAs and mRNAs are expressed in a stage-dependent manner, consistent with previous studies [ 35 , 36 , 37 ]. The results of both hierarchical clustering and PCA showed that the GRI and MGI stages were more distinct than MGI and RSI stages at the mRNA or lncRNA level ( Figure 2 ), implying that a massive physiological change related to a shift in metabolism occurred during early muscle development.…”
Section: Discussionsupporting
confidence: 93%
“…This complicated process of events requires a highly orchestrated program of gene expression and is regulated by various factors. According to the present study, lncRNAs and mRNAs tended to display a stage-dependent expression profile, consistent with other studies [ 36 , 37 , 38 ]. Hierarchical clustering and t-SNE analyses demonstrated that expression profiles between the ZT20 and ZT12 stages were markedly different from those of the ZT12 and ZT0 stages ( Figure 2 a,b), suggesting that the expression changes of lncRNAs and mRNAs were associated with serum LH level during the ovulatory cycle.…”
Section: Discussionsupporting
confidence: 93%
“…According to the present study, lncRNAs and mRNAs are expressed in a stage-dependent manner, consistent with previous studies [34][35][36]. The results of both hierarchical clustering and PCA showed that the GRI and MGI stages were more distinct than MGI and RSI stages at the mRNA or lncRNA level (Fig.…”
Section: Discussionsupporting
confidence: 92%